Evaluation of miscible and immiscible CO2 injection in one of the Iranian oil fields - Aref Hashemi Fath; Abdol-Rasoul Pouranfard (Egyptian Journal of Petroleum)
Carbon dioxide (CO2) flooding is one of the most important methods for enhanced oil recovery (EOR) because it not only increases oil recovery efficiency but also causes a reduction of greenhouse gas emissions. It is a very complex system, involving phase behavior that could increase the recovery of oil by means of swelling, evaporation and decreasing viscosity of the oil. In this study, a reservoir modeling approach was used to evaluate immiscible and miscible CO2 flooding in a fractured oil field. To reduce simulation time, we grouped fluid components into 10 pseudo-components. The 3-parameter, Peng–Robinson Equation of State (EOS) was used to match PVT experimental data by using the PVTi software. A one-dimensional slim-tube model was defined using ECLIPSE 300 software to determine the minimum miscibility pressure (MMP) for injection of CO2. We used FloGrid software for making a reservoir static model and the reservoir model was calibrated using manual and assisted history matching methods. Then various scenarios of natural depletion, immiscible and miscible CO2 injection have been simulated by ECLIPSE 300 software and then the simulation results of scenarios have been compared. Investigation of simulation results shows that the oil recovery factor in miscible CO2 injection scenario is more than other methods.